(3CeGdi GHf OQjOs - (3GHf OQjO , CHh HcQ eMeO Hf GdMSf Hf OQjO GdCROj, GHf OQjO,J (B321 (3g` s ((3eOjfI OeTb s)
(3ChdgG (B:s
(3bGd CHh HcQ Hf OQjO (B: (3CNHQfG CHh YKeGf , Yf GdJhRi Yf CHj YHjOg bGd (B: (3deG cGf jhe GdLed hGdJbi GdfGS NQL QLd ef Hfi CSO s
(3BNQgG (B:s
(3abGd (B: (3CfJ jG CejQ GdeDefjf cfJ CMb HgG , aCeG GdCf abGFdgG CMb HgG gPG BNQ GdLRA GdSGHY ef CeGdi GHf OQjO hGdMeO ddg QH GdYGdejf s
(3QhGjI CHh eSde eMeO Hf CMeO Hf Ydi GdcGJHs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B80 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B189 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B32s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs